Surgical treatment of autosomal recessive bestrophinopathy with angle-closure glaucoma: vitreous liquefaction as the key to correcting postoperative malignant glaucoma—three case reports - Sun, Zhonghua; Liu, Cuijuan; Liu, Wei; Zhang, Miaomiao; Ren, Shanshan; Gao, Lei; Ji, Zhen (Frontiers in Medicine, 2025)
PurposeThis study aimed to evaluate the surgical treatment of autosomal recessive bestrophinopathy (ARB) combined with angle-closure glaucoma (ACG) through a retrospective case series.MethodsThe treatment of three patients with ACG secondary to ARB was reviewed. The patients were admitted to the Department of Ophthalmology of Jinan Second People’s Hospital from April 2023 to January 2024. Their conditions, treatments, and outcomes were extracted from the medical records and analyzed.ResultsThe patients were 48, 48, and 35 years old at the time of surgery. All had bilateral ARB and underwent surgery in the eye more severely affected by ACG. Topical eye drops failed to control the intraocular pressure (IOP), which measured 27, 28, and 47 mmHg before the surgery. The affected eyes also exhibited a shorter axial length (AL) and shallower anterior chamber depth (ACD). The ALs of the surgical eyes measured 22.73 mm, 21.52 mm, and 20.96 mm, while the ACDs were 2.51 mm, 1.97 mm, and 2.19 mm, respectively. After receiving trabeculectomy, they all immediately developed malignant glaucoma, which could not be resolved by conservative treatment. Following a second surgery, which importantly included an anterior vitrectomy and posterior capsulotomy, the IOP was normal, the ACD was satisfactory, and visual function was preserved.ConclusionFor ACG/ARB patients, the risk of developing malignant glaucoma after glaucoma surgery is very high. Surgical intervention, such as anterior vitrectomy, is needed to increase vitreous fluidity, eliminate vitreous block, assist the formation of the anterior chamber, and stabilize the IOP to save the patient’s vision. Long-term, close follow-up is essential due to the risk of recurrence in the operated eye and occurrence in the non-operated eyes.